(untitled) (Bangladesh Journal of Botany, 2022)
The levels of cadmium (Cd) in soil and commonly consumed tomato (Lycopersicon csculentum Miller) fruits grown around the industrial areas of Dhaka and Narsingdi districts of Bangladesh were quantified and compared the levels with FAO/WHO (2003)safety limits. According to the findings, the order of Cd concentration in soils and tomato fruits was found around the Textile > Pharmaceutical > Tannary industry. The concentration (mg/l) of Cd in soil and tomato ranged from 0.24 to 0.91 and 0.15 to 0.74, respectively. Except Tannery industry levels of Cd in soil and tomato were exceeded the premise limit proposed by joint FAO/WHO. In all sites, the bioconcentration factor (BCF) for this heavy metal in tomatoes was found to be below 1, a sign of low uptake of heavy metals in the tomatoes from the soil. Results suggest that consumption of these tomatoes might cause health risk the consumers. Bangladesh J. Bot. 51(4): 729-736, 2022 (December)